Temporal trends in overweight and obesity of children and adolescents from nine Provinces in China from 19912006 - Cui, Z.; Huxley, Rachel; Wu, Y.; Dibley, M. (Informa Healthcare, 2010)
Objectives. To assess temporal changes in mean body mass index (BMI) and the impact of socio-economic status on the prevalence of overweight and obesity among Chinese children and adolescents in nine provinces between 1991 and 2006. Methods. Analysis of height and weight data in children and adolescents aged 717 years with complete information on age, gender, region, height and weight from consecutive China Health and Nutrition Surveys (CHNS). Measurements were recorded in 1991, 1993, 1997, 2000, 2004 and 2006. Household income data in 2006 were included in the analysis of the impact of socio-economic status on the prevalence of overweight and obesity in children and adolescents. BMI cut-offs recommended by IOTF were used to define childhood overweight and obesity, as well as the Chinese cut-offs. The Cochrane-Mantel-Haenszel test for trend was used to examine the temporal trends in the prevalence of childhood overweight and obesity. Generalised estimating equations analysis was performed to assess the changes in BMI during the study period after adjusting for age, sex, region and income. Results. In Chinese children and adolescents mean BMI steadily increased from 17.4 kg/m2 (95% CI: 17.317.5) in 1991 to 18.3 kg/m2 (95% CI: 18.118.5) in 2006, after adjusting for age, sex, region and income level. There was a corresponding increase in the prevalence of overweight and obesity from 5.2% in 1991 to 13.2% in 2006. The greatest increase occurred among male children and adolescents in whom the prevalence of excess body weight tripled from 4.8% in 1991 to 15.4% in 2006, compared with 5.4% and 11.0% in females over the same period. In 2006, those from higher income families tended to have the highest prevalence of overweight and obesity. Conclusions. The prevalence of overweight and obesity among Chinese children and adolescents has increased steadily over the past 15 years with the increase being apparent in all age, sex and income groups. However, the most noticeable increase was in children from urban areas and those from higher income backgrounds. © 2010 Informa Healthcare.